Second International Self-Reported Delinquency Study, 2005-2007 - Enzmann, Dirk ([Verlag nicht ermittelbar], 2015)
The Second International Self-Report Delinquency Study (ISRD-2) was a large international collaborative study of delinquency and victimization of 12 to 15 year-old students in seventh, eighth, and ninth grade classrooms. The study was a school-based study that drew on random samples from either city level or national level. In general, the cross-national description of the prevalence and incidence of delinquent behavior allowed for the assessment of national crime rates by comparison with the crime rates of other countries. The study was conducted in 31 mostly European countries, the United States, Caribbean and South American countries. The primary research questions explored included: Is juvenile delinquency normal, ubiquitous, and transitional? Is there a pattern of similarity in the offending behavior of juveniles across countries or are there any important differences? Descriptive comparisons of crime rates will call for explanations, especially if differences are observed. What are the national socio-economic or cultural differences, or the characteristics of legal or criminal policies that can explain such differences?